Fatigue induced by a cross-country skiing KO sprint - Zory, R.; Millet, G.; Schena, F.; Bortolan, L.; Rouard, A. (Medicine & Science in Sports & Exercise, 2006)
Purpose: The aims of the present study were 1) to analyze whether the KO sprint simulation induced a phenomenon of fatigue of upper and lower limbs and 2) if there was any fatigue, to determine its origin. Methods: Seven elite male skiers were tested before and after a simulation of KO sprints consisting of three 1200-m laps separated by 12 min of recovery. Surface electromyographic activity and force obtained under voluntary and electrically evoked contractions (single twitch) on knee-extensor muscles were analyzed to distinguish neural adaptations from contractile changes. A maximal power output test of the upper limbs was also performed. Results: During the last lap, the final sprint velocity was significantly lower than during the first lap. After the KO sprint, knee-extensor voluntary (-9.8 +/- 9.5%) and evoked (-16.2 +/- 11.9%) isometric force and upper-limb power output (-11.0 +/- 9.3%) and force (-11.3 +/- 8.7%) significantly decreased, whereas the blood lactate concentration increased to 11.6 mM. On the other hand, no changes were seen in RMS measurement during maximal voluntary contractions, RMS normalized by M-wave amplitude, or M-wave characteristics. Conclusion: Changes in performance, lactate concentration, knee-extensor strength, and upper-limb power indicated that the KO sprint test led the skiers to a state of fatigue. On lower-limb muscles, the decrease of knee-extensor strength was exclusively caused by peripheral fatigue, which was at least in part attributable to a failure of the excitation-contraction coupling.